2012
DOI: 10.1055/s-0032-1316775
|View full text |Cite
|
Sign up to set email alerts
|

Access to Aromatic Ring-Fused Benzimidazoles Using Photochemical Substitutions of the Benzimidazol-2-yl Radical

Abstract: Photochemical five-, six-, and seven-membered cyclizations from 2-iodo-1-(ω-arylalkyl)-1H-benzimidazoles are described. This method of producing aromatic ring-fused benzimidazoles is significantly more efficient than literature radical protocols using chemical initiators, although 2-iodo-1-(ω-pyridin-2-ylalkyl)-1H-benzimidazoles preferentially undergo a nucleophilic ipso-substitution onto the benzimidazole-2-position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“… 25 The photochemistry of 2-iodo-substituted BzIm yields aromatic ring-fused benzimidazoles via substitutions of the benzimidazol-2-yl radical. 26 The latter finding agrees with the report of Cole et al , 24 who found that 2-alkylbenzimidazoles do not give dimers but produce a mixture of acyl derivatives. N1-protonated benzopyrazoles 27 , 28 and benzisothiazoles were found to undergo isomerizations to the corresponding benzimidazoles and benzothiazoles ( Scheme 1 a).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“… 25 The photochemistry of 2-iodo-substituted BzIm yields aromatic ring-fused benzimidazoles via substitutions of the benzimidazol-2-yl radical. 26 The latter finding agrees with the report of Cole et al , 24 who found that 2-alkylbenzimidazoles do not give dimers but produce a mixture of acyl derivatives. N1-protonated benzopyrazoles 27 , 28 and benzisothiazoles were found to undergo isomerizations to the corresponding benzimidazoles and benzothiazoles ( Scheme 1 a).…”
Section: Introductionsupporting
confidence: 89%
“… 30 32 Interestingly, photoisomerizations opposite to those shown in Scheme 1 have not been reported. Although some reports about the photochemistry of benzimidazole in condensed media have already been published, 24 26 , 33 to the best of our knowledge, there are no reports on its photoinduced unimolecular transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Diastereoselectivity was not measured in the present UV-initiated reactions, but spectroscopic data for cycloadducts 3a , 3d and 3e (isolated in 17%–23% yield) matched the literature [5]. Aryl radical reduction products presumably formed by hydrogen abstraction from the solvent (acetonitrile [22,23,24]) were also detected, but not isolated and quantified. Yields of ( E )-3-ylideneoxindole acetates 2a and 2d – 2e were improved (55%–72%) when the acetonitrile reaction solvent was replaced by methanol (Scheme 3), which may partly be due to the absence of aryl radical reduction from the solvent.…”
Section: Resultssupporting
confidence: 62%
“…As part of this collaboration we became interested in forming the oxindole skeleton in the absence of toxic and hazardous radical initiators or expensive metal catalysts [22,23,24]. In this article, an “initiator and metal-free” photochemical radical pathway giving non-reduced adducts, ( E )-3-ylidene- oxindoles, after 5- exo - trig cyclization is reported (Scheme 3 and Scheme 4).…”
Section: Introductionmentioning
confidence: 99%